Micro-Level Determinants of Informal Employment in Turkey: A Logistic Regression Analysis - Dalyan, Sera Yildirim (Deniz Publication, 2025)
Since the 1980s, globalization and the diffusion of neo-liberal economic policies have reshaped labor markets and employment relations, generating enduring structural shifts that continue to influence patterns of informality. Identifying the micro-level determinants of informal employment is essential for designing effective policy interventions, as informality remains both a persistent global challenge and a core concern for social welfare systems. This study investigates the influence of individual and workplace characteristics on the likelihood of informal employment in Turkey. Drawing on microdata from the Household Labour Force Survey (HLFS) conducted by TURKSTAT between 2011 and 2015, a period marked by post-crisis stability and relative structural homogeneity, a logistic regression model is employed to estimate the probability of informal work. The model incorporates fifteen variables capturing demographic attributes (gender, age, education, marital status), employment status, firm-level features, number of employees, occupational position, managerial responsibility, and the extent to which work is performed at home. The findings reveal significant associations between informal employment and the majority of micro-level factors, with the exceptions of marital status, job search method, mode of working, job continuity, and home-based work, which do not exhibit statistically significant effects. These results provide robust empirical evidence for policymakers, highlighting which individual and workplace dynamics should be prioritized when formulating strategies to reduce informality. © 2025 Journal of Organizational Behavior Research.
Keywords: Informal economy; Informal employment; Labour market; Logistic regression; Micro determinants